Postpartum Hospital Readmissions With and Without Severe Maternal Morbidity Within 1 Year of Birth, Oregon, 2012–2017. Issue 2 (21st October 2022) - Kaufman, Menolly; McConnell, K John; Carmichael, Suzan L; Rodriguez, Maria I; Richardson, Dawn; Snowden, Jonathan M
Abstract: Postpartum readmissions (PPRs) represent a critical marker of maternal morbidity after hospital childbirth. Most severe maternal morbidity (SMM) events result in a hospital admission, but most PPRs do not have evidence of SMM. Little is known about PPR and SMM beyond the first 6 weeks postpartum. We examined the associations of maternal demographic and clinical factors with PPR within 12 months postpartum. We categorized PPR as being with or without evidence of SMM to assess whether risk factors and timing differed. Using the Oregon All Payer All Claims database, we analyzed hospital births from 2012–2017. We used log-binomial regression to estimate associations between maternal factors and PPR. Our final analytical sample included 158, 653 births. Overall, 2.6% ( n  = 4, 141) of births involved at least 1 readmission within 12 months postpartum (808 (19.5% of PPRs) with SMM). SMM at delivery was the strongest risk factor for PPR with SMM (risk ratio (RR) = 5.55, 95% confidence interval (CI): 4.14, 7.44). PPR without SMM had numerous risk factors, including any mental health diagnosis (RR = 2.10, 95% CI: 1.91, 2.30), chronic hypertension (RR = 2.17, 95% CI: 1.85, 2.55), and prepregnancy diabetes (RR = 2.85, 95% CI: 2.47, 3.30), all which were on par with SMM at delivery (RR = 1.89, 95% CI: 1.49, 2.40).